Zinc or/and Vitamin E Supplementation Mitigates Oxidative Stress, Neuroinflammation, Neurochemical Changes and Behavioural Deficits in Male Wistar Rats Exposed to Bonny Light Crude Oil - Oluwafunmbi Ebenezer Ogunmiluyi; Alexander Obidike Naiho; Victor Oghenekparobo Emojevwe; Tolulope Samuel Oladele; Kayode Adedoyin Adebisi; Jacob Adewale Siyanbade; Adeniran Oluwadamilare Akinola (Journal of Toxicology)
Conclusion: Treatment with Zn and/or vitamin E reverses BLCO-induced neurobehavioural alterations via modulation of oxidative stress, inflammation and neurotransmitters.